Hypersensitivity may be involved in severe COVID‐19. Issue 2 (9th October 2021) - Tan, Cuiyan; Zheng, Xiaobin; Sun, Fengfei; He, Jianzhong; Shi, Honglei; Chen, Meizhu; Tu, Changli; Huang, Yiying; Wang, Zhenguo; Liang, Yingjian; Wu, Jian; liu, Ye; et al.
Abstract: Background: Deaths attributed to Coronavirus Disease 2019 (COVID‐19) are mainly due to severe hypoxemic respiratory failure. Although the inflammatory storm has been considered the main pathogenesis of severe COVID‐19, hypersensitivity may be another important mechanism involved in severe cases, which have a perfect response to corticosteroids (CS). Method: We detected the serum level of anti‐SARS‐CoV‐2–spike S1 protein‐specific IgE (SP‐IgE) and anti‐SARS‐CoV‐2 nucleocapsid protein‐specific IgE (NP‐IgE) in COVID‐19. Correlation of levels of specific IgE and clinical severity were analysed. Pulmonary function test and bronchial provocation test were conducted in early convalescence of COVID‐19. We also obtained histological samples via endoscopy to detect the evidence of mast cell activation. Result: The levels of serum SP‐IgE and NP‐IgE were significantly higher in severe cases, and were correlated with the total lung severity scores (TLSS) and the PaO2 /FiO2 ratio. Nucleocapsid protein could be detected in both airway and intestinal tissues, which was stained positive together with activated mast cells, binded with IgE. Airway hyperresponsiveness (AHR) exists in the early convalescence of COVID‐19. After the application of CS in severe COVID‐19, SP‐IgE and NP‐IgE decreased, but maintained at a high level. Conclusion: Hypersensitivity may be involved in severe COVID‐19. Abstract : Level of IgE to SARS‐CoV‐2–spike protein and nucleocapsid protein positively correlated with clinical severity in COVID‐19 patients. Airway hyperresponsiveness (AHR) exists in early convalescence of COVID‐19. Mast cells with concurrently positive staining for IgE and CD63 were observed in lamina propria of the bronchus and duodenum in severe COVID‐19. We deduce that hypersensitivity reaction may be involved in severe COVID‐19. Note: SP‐IgE: anti‐spike protein (SP) IgE; NP‐IgE: anti‐nucleocapsid protein (NP) IgE; TLSS: Total lung severity scores; BPT: bronchial provocation test; Reff: effective airway resistance; R5‐R20: difference between the resistance at 5 Hz and 20 Hz.